FREQUENCY OF EMOTIONAL EXPRESSIONS IN YOUTH SPEECH - Atajonova, Gulonoza (International Conference on Linguistics & Translation, 2025)
This thesis examines the frequency of emotional expressions in youth speech from a psycholinguistic perspective. The study analyzes how often and in what communicative functions emotional units are used in both spoken and written speech. Furthermore, it explores the functional significance of emotional expressions in youth speech and their relationship with personal and social factors. The findings demonstrate that youth speech is emotionally rich and dynamic.